PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PERJANJIAN KERJA DENGAN SISTEM OUTSOURCING MENURUT UU NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Muh Rizki Syafaat (Fakultas Hukum Universitas Muhammadiyah Palu, 2017)
Changes in the application of modern technological results are now widely cited as one of the causes for the occurrence of social change, including in the field of labor law. In the Act No. 13 of 2003 on Manpower does not mention explicitly about terms and outsourcing. The outsourcing model can be compared with the form of the charter agreement although it is not the same. The charter agreement can be likened to a regular contract system, while outsourcing itself is not a contract. Workers / laborers in the charter agreements can be likened to casual workers as stipulated in the Regulation of the Minister of Manpower NR: PER. 06 / MEN / 1985 on Protection of Daily Workers (PHL). PHL is a worker who works for an employer to do a particular job and may vary in time and volume of work by receiving wages based on daily attendance of the worker. Keywords :